2020
DOI: 10.2139/ssrn.3632684
|View full text |Cite
|
Sign up to set email alerts
|

Improving Tax Compliance Without Increasing Revenue: Evidence From Population-Wide Randomized Controlled Trials in Papua New Guinea

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The general provisions of taxation have been regulated in law (Hoy et al, 2020). In order for tax regulations to be obeyed by taxpayers, there must be strict tax sanctions for those who violate them.…”
Section: Sanctions and Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…The general provisions of taxation have been regulated in law (Hoy et al, 2020). In order for tax regulations to be obeyed by taxpayers, there must be strict tax sanctions for those who violate them.…”
Section: Sanctions and Compliancementioning
confidence: 99%
“…The results showed that tax socialization, tax knowledge, service quality, tax sanctions and tax awareness had a positive effect on motor vehicle taxpayer compliance. In addition, it is also relevant to research conducted by (Alasfour, 2019;Hoy et al, 2020) With the results of the research showing that taxpayer awareness, tax knowledge, taxation sanctions and public service accountability have a positive effect on taxpayer compliance in paying motorized vehicle taxes.…”
Section: Tax Awareness Of Tax Compliancementioning
confidence: 99%